Morphological and genetic characterisation of Pagliarola breed and its genetic relationships with other three indigenous Italian sheep breeds. Issue 1 (2nd January 2016) - Ceccobelli, Simone; Di Lorenzo, Piera; Panella, Francesco; Lasagna, Emiliano; Sarti, Francesca M.
Abstract: Sheep are an important livestock species in the socio-economic contest around the world. In the past, exotic sheep breeds were utilised in crosses with local breeds in order to improve their production traits. The Pagliarola is an ancient sheep population spread over many areas of the central Italy, mainly in Abruzzo region. The aim of this paper was to identify this breed from other sheep breeds living in the same area trough morphological and genetic characterisation. Fifty-three Pagliarola sheep animals (two flocks) were sampled together with 30 sheep of Appenninica, Gentile di Puglia and Merinizzata Italiana. Biometrical measures and 25 microsatellite markers were studied for the characterisation. In the morphological analysis, the Pagliarola was observed to be well separated from the other breeds and the genomic results confirmed the morphological study. In the molecular approach, a total of 330 alleles were detected. In the neighbour-Net tree, each breed clustered independently and no clear cluster was observed. The expected heterozygosity was the highest in Appenninica (0.78), while Pagliarola had the lowest (0.70). Results of STRUCTURE analyses at K =5 showed Pagliarola breed splitted in two sub-clusters. Both biometric and molecular results allow to consider the residual Pagliarola as an original genotype. Moreover, the variability still remaining in this population can be useful to plan suitable conservation programs.